A comprehensive fracture research of an aircraft swash-plate pump. (October 2022) - Saracyakupoglu, Tamer
Highlights: Failure analysis of an aircraft swash-plate pump was performed. On the inner race surface of bearing and piston shoes, an al-based pollutant substance has been discovered. All the parts were inspected using Field Emission Scanning Electron Microscope (SEM) and Energy-Dispersive X-ray Spectroscopy (EDX). The bearing failure has created all damage in the subparts of the pump. Abstract: Aviation pumps are widely used to feed the actuators of the components such as the aileron, flap, slat, rudder, elevator, and landing gear of an aircraft. The swash-plate pumps are the most popular ones of the aviation pumps. This study analyses the failure of a jet aircraft's swash-plate pump mounted on the inner wing and has the function of feeding the flap actuators. After the pump's failure had been discovered and an investigation was performed. At first, the Foreign Object Damage (FOD) originated from a foreign particle carried by hydraulic flow attracted the doubts. But after further fractographic analysis, it was shown that a micro-crack on the slipper retainer holes had initiated the asymmetric loads and led to cross-section friction on the Swash-Plate surface. It was an Inner Object Damage (IOD). Some suggestions for preventing the lack of lubrication in the slipper retainer holes are given in this paper.